Perfil sensorial de cachaça utilizando diferentes metodologias com consumidores - Costa, Vanderson da Silva (2018)
Descriptive sensory analysis, such as Quantitative Descriptive Analysis - ADQ - are the most common tools used to evaluate the sensory properties of foods and beverages. However, they are time-consuming and expensive techniques that use sensory panels, trained tasters or experts. alternatives were developed to gain time and minimize these limitations. Thus, this work aims to construct a sensorial profile of cachaça from the application of the CATA test with a scale of unstructured intensity, in a quantitative descriptive way, having as evaluators, consumers of cachaça. Six brands of commercial cachaça were defined according to a qualitative questionnaire applied with consumers, taking into account the most consumed brand, origin and characteristics appreciated. Two focus group sessions were held to survey attributes. The CATA methodology was applied with a scale of unstructured intensity of nine centimeters, the "Multiple Factor Analysis" was used to study the characterization and discrimination of the cachaças made by the evaluators with the data of continuous scale. Quality physicochemical analyzes were performed. The overall impression was analyzed. We applied the ACP to construct the Preference Internal Map and the Cluster analysis with Euclidian distance and Ward method. 203 people participated in the qualitative questionnaire phase. Among the terms generated in the focus group, 13 were used to assemble the CATA file, where 82 tasters participated in the tests. According to the GPA, 79.31% of the data were obtained in the two dimensions, where the attributes analyzed were residual sweet taste, sweet flavor, woody flavor, sweet aroma, sweet aroma, which counterpoint the axis negative effect of the first dimension that presents as highly discriminating the aroma of alcohol. Other attributes related to the impact of the drink in the mouth and path to the stomach were the residual alcoholic flavor, aggressiveness, burning and residual wood flavor. Thus, the CATA with an unstructured intensity scale proved to be efficient to differentiate, by segmenting the categories of cachaças and differentiating them within the category itself, presenting itself as an important descriptive and quantitative tool to be applied with consumers, to the construction of a sensorial profile with a language of the consumers.